Metallic Stents for Proximal Tracheal Stenosis: Is It Worth the Risk? - Sandeep Bansal; Shruti Dhingra; Babita Ghai; Ashok K. Gupta (Case Reports in Otolaryngology)
Objective. To demonstrate the risk associated with blocked proximal tracheal stents when a patient presents with acute respiratory distress, with blockage of stent and what is the best management we can offer without damage to the stent and its associated complications. Case Report. A 22-yr-old, male patient, presented in severe respiratory distress. He had history of corrosive poisoning for which he was tracheotomised. A stainless steel wire mesh stent was placed in the trachea, from the subglottis, to just above the carina. One month later, he presented with a critically compromised airway with severe respiratory distress. Emergency tracheostomy was done and the metallic stent had to be cut open, in order to provide an airway. Conclusion. Management of blocked proximal stents with patient in respiratory distress remains a challenge. Formation of granulation tissue is common and fibreoptic bronchoscopic assisted intubation may not always be possible. A regular follow up of all patients with stents is essential. Placement of stents within a few centimetres of cricotracheal junction should not be encouraged for long term indications.